Descriptive Epidemiology of Head and Neck Squamous Cell Carcinoma in Puerto Ricans - Almodovar, José; Perez, Sara J.; Arruza, Michael; Morell, Carlos A.; Baez, Adriana (Puerto Rico Health Sciences Journal, 2025)
see manuscript